2019
DOI: 10.1115/1.4043417
|View full text |Cite
|
Sign up to set email alerts
|

Springtail-Inspired Triangular Laser-Induced Surface Textures on Metals Using MHz Ultrashort Pulses

Abstract: Considering the attractive surface functionalities of springtails (Collembola), an attempt at mimicking their cuticular topography on metals is proposed. An efficient single-step manufacturing process has been considered, involving laser-induced periodic surface structures (LIPSS) generated by near-infrared femtosecond laser pulses. By investigating the influence of number of pulses and pulse fluence, extraordinarily uniform triangular structures were fabricated on stainless steel and titanium alloy surfaces, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…25 below illustrates laser induced morphological profiles for silicon, after static irradiations with cylindrically polarized optical vortexes generated via a q-plate. Furthermore, circularly polarized ultrafast laser pulses are recently utilized to fabricate triangular periodic surface structures on metal surfaces [185,258] which can be used for inducing uniform iridescence of laser structured metallic surfaces.…”
Section: Complex Polarization Statesmentioning
confidence: 99%
“…25 below illustrates laser induced morphological profiles for silicon, after static irradiations with cylindrically polarized optical vortexes generated via a q-plate. Furthermore, circularly polarized ultrafast laser pulses are recently utilized to fabricate triangular periodic surface structures on metal surfaces [185,258] which can be used for inducing uniform iridescence of laser structured metallic surfaces.…”
Section: Complex Polarization Statesmentioning
confidence: 99%
“…Typically, the LSFL period is close to the laser wavelength (λ), while the HSFL period is smaller than λ/2 [10]. A significant step forward to control the structure morphologies, in order to fabricate biomimetic textures [11], was achieved with the production of LSFL having 2D symmetry (2D-LIPSS), thanks to the use of different polarization states of the incident radiation [12,13] and to complex irradiation strategies [14]. Double-pulse irradiation (DPI) has shown the formation of a variety of structures in molybdenum [15] and in steel [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Although the substrate material from this study differs from the studies by Romano et al [26,39] (X6Cr17 ferritic stainless steel), the physical characteristics, such as texture periodicity, symmetry and general morphology, appear almost identical, therefore, suggesting similar functional performance is to be expected (Figure 2 & Figure 3). However, wettability testing (functional property) carried out within this study does not follow the same trend as previously observed, with stabilised (3 months) water contact angle readings decreasing following triangular LIPSS texturing of the untreated 316L ASS samples (UntΔ; Table 3).…”
Section: Properties Of Triangular Lipss Texturesmentioning
confidence: 51%
“…Under the right conditions, instead of ripple-like features, triangular shaped and hexagonally organised pillars, resembling the surface of springtails, are formed with similar periodicity to LSFL in 3 different directions [26,39]. Due to the near nanoscale features and high hydrophobicity, these new structures, named triangular LIPSS, are promising for antibiofouling applications, and studies on similar structures have produced excellent results [41].…”
Section: Page 8 Of 49mentioning
confidence: 99%
See 1 more Smart Citation